Degenerescência caseosa da calcificação do anel mitral: uma perspectiva multi-imagem - Ribeiro, S (2012)
Mitral annulus calcification is a common echocardiographic finding, particularly in the elderly and in end-stage renal disease patients under chronic dialysis. Caseous calcification or liquefaction necrosis of mitral annulus calcification is a rare evolution of mitral annular calcification. Early recognition of this entity avoids an invasive diagnostic approach, since it is benign and, unlike intracardiac tumors and abscesses, has a favorable prognosis. The authors present the case of an 84-year-old woman with a suspicious large, echodense mass at the level of the posterior mitral leaflet with associated severe mitral regurgitation. Cardiac magnetic resonance imaging demonstrated a hypoperfused mass with strong peripheral enhancement 10 minutes after gadolinium administration. Multislice computed tomography showed the calcified nature of the mass. A multi-modality imaging approach confirmed the diagnosis of caseous calcification of the posterior mitral annulus. The patient refused surgical treatment.